2017
DOI: 10.1634/theoncologist.2017-0257
|View full text |Cite
|
Sign up to set email alerts
|

Individual Trade-Offs Between Possible Benefits and Risks of Cancer Treatments: Results from a Stated Preference Study with Patients with Multiple Myeloma

Abstract: The objectives of this study were to ascertain the treatment preferences of patients with multiple myeloma, considering benefits and risks of particular cancer treatments, and to illustrate how such data may be used to estimate patients' acceptance of new treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 8 publications
5
49
0
Order By: Relevance
“…Two other studies that used ASW to elicit patient preferences have been published 26 , 27 . Both studies also observed substantial preference heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Two other studies that used ASW to elicit patient preferences have been published 26 , 27 . Both studies also observed substantial preference heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, Q-TWiST analyses help to fill a gap in our understanding of the tradeoffs in clinical risk and benefit of various oncology therapies from a patient perspective. These tradeoffs are receiving increasing attention from regulators and physicians, including the European Medicine Agency, [23][24][25] the US Food and Drug Administration, 26 and the American Society of Clinical Oncology, 27 which formally define a net health benefit score based on clinical benefits and toxicities. The Q-TWiST approach makes it possible for any physician or patient to tailor the results to his or her own personal value placed on TOX, TWiST, and REL and adapt the survival analysis to reflect his or her own personal situation and beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…Development of theoretically sound benefit‐risk models is not easy and elicitation of stakeholder preferences for such models needs to account for critical study success factors, which are dependent on the chosen elicitation methodology . Preferences can be elicited efficiently with methods such as DCE, choice‐based matching, threshold technique, or swing weighting, and the most appropriate method is dependent on characteristics of the benefit‐risk assessment . Most elicitation methods result in preferences being measured on utility scales that can be difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%